Subsidiary Roles on the MNC Strategy - Stajanoska, Irene; Tulung, Joy Elly (Universitas Prasetiya Mulya, 2008)
This article is a conceptual and typological framework that delineates the subsidiary role and its influence on the MNC strategy. The purpose of this study is two fold. First we want to formulate proposition for testing the relationship between the network embeddedness, resource dependence and subsidiary influence on the corporate strategy. Secondly we want to suggest a typology for determination of the specific characteristics of subsidiaries that are simply implementors of HQ assigned strategy, have a global subsidiary mandates or are somewhere in between. Finally the article suggests direction for future research.